Ancient history : key themes and approaches - Morley, Neville (Routledge key guides., 2000)
Ancient History is a sourcebook of writings on ancient history. It offers an invaluable introduction to the most important ideas, theories and controversies, and a thought-provoking survey of the range of views and approaches.